ANALISIS BEBAN KERJA PETUGAS DI UNIT BPJS CENTER RUMAH SAKIT KRAKATAU MEDIKA KOTA CILEGON DENGAN METODE WORK SAMPLING - Risa Rahayu; Ayun Sriatmi; Septo Pawelas Arso (Jurnal Kesehatan Masyarakat (Undip), 2017)
BPJS Kesehatan have to maintain quality control and cost control. As an effort to realize the management of BPJS patient claims that quality are closely related to the quantity and quality of personnel in the BPJS Center Unit. This study analyzes the workload and manpower needs in the BPJS Center Krakatau Medika Hospital Cilegon City. Work sampling method used for measure the workload, while the method Workload Indicator Staffing Needs (WISN) is used for measure the power requirements based on actual workload. Work sampling conducted on May 15 – June 2 2017. The results of this study indicate that the Administrator personel who have been using 80,31 % of the work time with productive activities. Of productive activity is, as much as 60,90% is for direct productive activities, 19,41% is for not directly productive activities. meanwhile 8,82% used for personal acitivities and 10,86 for unproductive activities. Work sampling results to Coder are 81,05% of the work time with productive activities, 61% is for direct productive activities and 20,05% is for not directly productive activities, for personal activities is 6,20% and 12,76% for unproductive activities. Based on the results of the work sampling, with WISN turns out that the current force is smaller than the power requirements to complete the tasks and functions of the BPJS Center Krakatau Medika Hospital Cilegon City.